Abduction and styles of scientific thinking. - Vitti Rodrigues, Mariana; Emmeche, Claus (Synthese, 2021)
In philosophy of science, the literature on abduction and the literature on styles of thinking have existed almost totally in parallel. Here, for the first time, we bring them together and explore their mutual relevance. What is the consequence of the existence of several styles of scientific thinking for abduction? Can abduction, as a general creative mode of inference, have distinct characteristic forms within each style? To investigate this, firstly, we present the concept of abduction; secondly we analyze what is understood by styles of thinking; thirdly, we give some comments on abduction and styles of thinking by analyzing examples of scientific discovery or innovation within each style. We develop a case-based comparative investigation of creative aspects of abductive reasoning with examples drawn from different styles of scientific thinking and doing as understood by the Crombie/Hacking tradition. We argue that abduction, as a general mode of reasoning, can have a variety of specific expressions enabled and constrained by the styles of scientific thinking. Finally, we draw some conclusions on the relationship between abduction and styles of thinking suggesting that scientific discovery is a dynamical goal-directed activity within the scientific community that benefits from distinct styles of thinking and doing research.